The effects of focused attention training (FOCAL) on the duration of novice drivers' glances inside the vehicle - Pradhan, A.K. (2011)
Several studies have documented that the failure of drivers to attend to the forward roadway for a period lasting longer than 2-3 seconds is a major cause of highway crashes. Moreover, several studies have demonstrated that novice drivers are more likely to glance away from the roadway than experienced drivers for extended periods when attempting to do a task inside the vehicle. The present study examines the efficacy of a PC-based training program (FOCAL) designed to teach novice drivers not to glance away for these extended periods of time. A FOCAL-trained group was compared to a placebo-trained group in an on-road test, and the FOCAL-trained group made significantly fewer glances away from the roadway that were more than 2 seconds than the placebo-trained group. Other measures indicated an advantage for the FOCAL-trained group as well.